2022
DOI: 10.3390/sym14020422
|View full text |Cite
|
Sign up to set email alerts
|

Topological Sigma-Semiring Separation and Ordered Measures in Noetherian Hyperconvexes

Abstract: The interplay between topological hyperconvex spaces and sigma-finite measures in such spaces gives rise to a set of analytical observations. This paper introduces the Noetherian class of k-finite k-hyperconvex topological subspaces (NHCs) admitting countable finite covers. A sigma-finite measure is constructed in a sigma-semiring in a NHC under a topological ordering of NHCs. The topological ordering relation maintains the irreflexive and anti-symmetric algebraic properties while retaining the homeomorphism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, this is a stronger condition for retaining ordering relations and it can be relaxed. Earlier, it was shown that two topological hyperconvex spaces can be ordered under a special topological-ordering relation affecting the measurability in such spaces [9]. A topological space X is Bolzano-Weierstrass space (B w − space) if every infinite subset of X has an accumulation point.…”
Section: Motivationmentioning
confidence: 99%
“…However, this is a stronger condition for retaining ordering relations and it can be relaxed. Earlier, it was shown that two topological hyperconvex spaces can be ordered under a special topological-ordering relation affecting the measurability in such spaces [9]. A topological space X is Bolzano-Weierstrass space (B w − space) if every infinite subset of X has an accumulation point.…”
Section: Motivationmentioning
confidence: 99%